Unrecognised scurvy. (17th September 2009) - Choh, Clarisa T P; Rai, S; Abdelhamid, M; Lester, W; Vohra, R K
Abstract : Take a careful dietary history to exclude scurvy in patients with unexplained musculocutaneous bleeding.